2015
DOI: 10.1002/cncy.21586
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon BRAF mutations in the follicular variant of thyroid papillary carcinoma: New insights

Abstract: BACKGROUND: Mutational analysis is reshaping the practice of fine-needle aspiration cytology for the diagnosis of thyroid nodules. The v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) valine (V) to glutamic acid (E) substitution at codon 600 (BRAF V600E ) is the most effective diagnostic/prognostic marker and is used mainly for papillary thyroid carci- KEY WORDS: BRAF mutations; follicular neoplasms; follicular variant of papillary thyroid carcinoma; liquid-based cytology; papillary thyroid carcinoma. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…10 In fact, although the histological detection of I-FVPTCs does not pose any problem in diagnosing them as carcinoma, there are some controversies with regard to the presence of encapsulated FVPTCs (NIFTPs), for which the diagnosis relies only on the nuclear features of PTC. [2][3][4][5][6][7][8][9]32,33 In these last months, other authors such as Ganly et al and Thompson also have demonstrated evidence that the majority of, if not all, the encapsulated FVPTCs (NIFTPs) do not have any recurrence and metastases after a follow-up of years and/or decades. 9,34 It is clear that encapsulated FVPTC is an indisputably overdiagnosed entity.…”
Section: Discussionmentioning
confidence: 99%
“…10 In fact, although the histological detection of I-FVPTCs does not pose any problem in diagnosing them as carcinoma, there are some controversies with regard to the presence of encapsulated FVPTCs (NIFTPs), for which the diagnosis relies only on the nuclear features of PTC. [2][3][4][5][6][7][8][9]32,33 In these last months, other authors such as Ganly et al and Thompson also have demonstrated evidence that the majority of, if not all, the encapsulated FVPTCs (NIFTPs) do not have any recurrence and metastases after a follow-up of years and/or decades. 9,34 It is clear that encapsulated FVPTC is an indisputably overdiagnosed entity.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of ICC, several authors* have confirmed that Hector Battifora mesothelial 1 (HBME-1) and galectin-3 show the highest specificity and sensitivity in diagnosing malignant lesions on LBC samples, although neither of these markers is so highly accurate to be recognized as the specific marker of malignancy. However, other authors [33][34][35][36][37][38][39][40][41][42] have emphasized the limitations and flaws of ICC (eg, low specificity), and have focused on the role of molecular testing as an additional aid to properly classify thyroid indeterminate nodules.…”
Section: Thyroidmentioning
confidence: 99%
“…Importantly, some of these alterations arise early in the tumorigenic process. [33][34][35][36][37][38][39] For instance, papillary thyroid carcinoma (PTC), the most common thyroid malignancy, may carry v-Raf murine sarcoma viral oncogene homolog B (BRAF), Ret proto-oncogene in PTC (RET/PTC), or rat sarcoma viral oncogene homolog (RAS) mutations. 33,34 A large number of prospective and retrospective studies have demonstrated the diagnostic role of somatic mutations and showed the high specificity of some of them (ie, BRAF mutations) as markers of cancer.…”
Section: Thyroidmentioning
confidence: 99%
“…For this latter marker, intense positivity of more than 80%‐90% of follicular cells is a rule out immunostaining for malignancy . More recent studies on the immunocytochemical detection of the protein associated with the BRAF V600E mutation using the antibody VE‐1 on FNACs specimen of the papillary thyroid carcinomas processed by LBC (Figure D) or cell blocks show a good correlation with the molecular testing results.…”
Section: Immunocytochemistry (Icc)mentioning
confidence: 86%